Development of an Anti-Adhesive Membrane for Use in Video-Assisted Thoracic Surgery - Uemura, Akiko (Int J Med Sci, 2018)
Background: The need to prevent postoperative adhesions after surgery has been considered a significant challenge in thoracic surgery, especially with the advent of video-assisted thoracic surgery (VATS). While preventive materials for postoperative adhesions have been studied for many years, they are all still in the development phases. Methods: In this animal study, an insoluble hyaluronic acid membrane was used in VATS for wedge resection to test its operability and to examine the body's response to the membrane. Ten beagles were divided into two groups, an experimental group and a negative control group. In the experimental group, an insoluble hyaluronic acid membrane containing glycerol was used as the test membrane (10 x 10 x 0.1 cm(3)). The test membrane was implanted in the left thoracic cavity of the animal under VATS following wedge resection. The animals were observed for two weeks and then euthanized for examination. Results: Macroscopically, the median adhesion score was lower in the experimental group (0) than in the control group (2.5). On histopathological examination, the test membrane elicited only a minor inflammatory response and foreign body reaction. Conclusion: The test membrane showed satisfactory operability and appears to be a practical material to prevent postoperative adhesions after thoracic surgery in VATS.